Tissue and spine regeneration in the temperate sea urchin Psammechinus miliaris. Issue 2 (3rd April 2017) - Brown, Leah R.; Caldwell, Gary S.
Abstract: The tissue regenerative capabilities of echinoderms are well known at the morphogenic level, yet significant knowledge gaps remain concerning the molecular control of these processes. This pilot study assayed two pharmacological agents (vincristine sulphate and DAPT) injected directly into the body cavity of specimens of the temperate echinoid Psammechinus miliaris which had had their spines and tube feet deliberately amputated. Vincristine sulphate, which is a generalised mitotic inhibitor, was used as a positive control, whereas DAPT is a y -secretase inhibitor known to block sea urchin embryo development and suppress echinoid regeneration by interfering with Notch signalling pathways. Significant differences in regeneration rate became apparent in both treatments 29 days post amputation with both inhibitors slowing regeneration of tube feet (0.6 μg/g vincristine sulphate by 44.4% relative to controls; 4 μg/g DAPT by 55.6% relative to controls) and spines (0.6 μg/g vincristine sulphate by 53.3% relative to controls; 4 μg/g DAPT by 66.7% relative to controls). Vincristine sulphate was more clearly dose-dependent than DAPT. This initial inhibition-based approach allows inferences to be made concerning possible molecular pathways controlling regeneration within P. miliaris and adds further support to the hypothesis that Notch signalling plays a major role in regulating regeneration in echinoids.